Laparoscopic and robot-assisted surgery in urology atlas of standard procedures - Stolzenburg, J. -U. (Jens-Uwe) 1964-.; Tèurk, Ingolf A.; Liatsikos, Evangelos N.; SpringerLink (Online service). (Berlin London Springer, 2011)
aOperative urology has evolved in recent years to include laparoscopic and robot-assisted surgical procedures, which have resulted in significant improvements in quality of life-related outcome. Nevertheless, training methods in urologic laparoscopy and robot-assisted surgery vary considerably, and a structured training scheme is required to enable the modern urologist to adapt to and make optimal use of these techniques. Accordingly, the main goal of this surgical atlas is to guide the urologist carefully through all the standard laparoscopic and robot-assisted procedures. Each procedure is presented in detail with numerous supporting endoscopic images and diagrams. The reader is thereby acquainted with the different surgical steps and will acquire the knowledge necessary for reliable reproduction of the techniques in clinical practice.
aIntroduction -- Upper urinary tract -- Lymphadenectomies -- Urinary bladder and prostate -- Female pelvic surgery -- Paediatric urology -- Miscellaneous.
Electronic reproduction.
Keywords: Genitourinary organs -- Surgery; Laparoscopic surgery; Surgical robots; Electronic books